IMPLIKASI PEMBELAJARAN BERBASIS PROYEK DALAM MENINGKATKAN PRESTASI BELAJAR SISWA: STUDI KASUS DI MADRASAH IBTIDAIYAH AL ISLAH TIUDAN KABUPATEN TULUNGAGUNG - Rizal Fuadiy, Moch.; Ferisalma Al Fauz, Moh. (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
The educational system in Indonesia prioritizes learning methodologies that foster active student engagement, supported by the adoption of the Merdeka Belajar Curriculum across all educational levels. Among these methodologies, project-based learning stands out. This study aims to investigate the implications of implementing project-based learning in the subject of Qur'an Hadith, with the goal of improving student learning outcomes at Madrasah Ibtidaiyah Al Islah Tiudan, Tulungagung Regency. Conducted from April to August 2023, the research employed a qualitative approach using a case study design. Data collection methods included observation, interviews, and field documentation, with subsequent analysis carried out through condensation techniques, data presentation, and inference drawing. Data validity was ensured through triangulation. Findings suggest that project-based learning offers students more meaningful learning experiences by engaging them in real-world projects, which are more stimulating compared to traditional passive approaches. Evaluation results indicate a noteworthy enhancement in student learning achievement following the implementation of project-based learning. In summary, project-based learning emerges as an effective strategy for improving the educational process in schools.